If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8y + 4 = 7y + -8 Reorder the terms: 4 + 8y = 7y + -8 Reorder the terms: 4 + 8y = -8 + 7y Solving 4 + 8y = -8 + 7y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-7y' to each side of the equation. 4 + 8y + -7y = -8 + 7y + -7y Combine like terms: 8y + -7y = 1y 4 + 1y = -8 + 7y + -7y Combine like terms: 7y + -7y = 0 4 + 1y = -8 + 0 4 + 1y = -8 Add '-4' to each side of the equation. 4 + -4 + 1y = -8 + -4 Combine like terms: 4 + -4 = 0 0 + 1y = -8 + -4 1y = -8 + -4 Combine like terms: -8 + -4 = -12 1y = -12 Divide each side by '1'. y = -12 Simplifying y = -12
| -12+8x=-6(8x+2)+5x | | 7y-4+6=2y+4 | | .6w+2=26 | | ln(13)-ln(2x)=ln(52) | | 3x^2-4=4x | | 8+8q=9+7q | | m^2+6m-91= | | -5=x/2-5 | | -8c+5=-2-4c | | 38-6b=4(4b+4) | | x+.80(2)=.90(x+2) | | 5x^2y^3(2xy^3+3x^4y)= | | 8-10x=84-38x | | x+47=7x-13 | | x^2-3x+4=5 | | -2-7p=1-7p | | -12+5k=2k+3 | | 2x-3=-2x+5 | | 9x-22=6x+11 | | -2(1+7x)=-8x-32 | | n/5=-12 | | 9x(x+9)= | | y/3=8 | | 2t-3+8=3t-8 | | x/4=-12 | | x^2-11x=(-28) | | 3-f=6f+24 | | 13-2x=7x+5 | | -7(3v+6)=-7v+28 | | -x-6=-x^2 | | -9w=54 | | -b=-6 |